Management, Challenges and Expectations For Expanding Access to Online Adult Education Programme - Boateng, J.K. (International Journal of Economics, Commerce and Management United Kingdom, 2015)
This study explored from an administrative perspective factors that posed challenges to adult learners and their expectations for expanding access to adult online education programme. Two Foci group discussions were to uncover feelings, attitudes, motivation, insights and perceptions about expectations and challenges potential adult learners faced in online learning. Two different groups were used for the discussion. Each group consisted of eight individuals and each discussion lasted for 90 minutes. A need for training in basic knowledge in computing for prospective adult learners was identified. Further, it was noted that, the adult learner must be taught to do online learning; to navigate through the online interface and on how to access earning materials online, complete assignments and participate in discussion forums using means that are motivating and involve simple instructions. It was suggested, administrators and academic leaders use this knowledge to address learners’ expectations and help shape success in online education.
Keywords: E-learning, Adult learners, Administrators perspectives, Online interface